Evaluation of the microbiological quality of cattle carcasses in some slaughterhouses at Benin, West Africa - DOUGNON, T. VICTORIEN; BABA-MOUSSA, FARID A. KADER SAÏD; BABA-MOUSSA, LAMINE SAÏD (My University, 2015)
Background: Slaughterhouse is one of the major critical points in meat hygiene with slaughtering being the stage of occurrence of most contamination risks. Methods: This study aimed to assess the microbiological quality of cattle carcasses in the slaughterhouses of Cotonou/Porto-Novo. Samples were collected by excision from four parts on each carcass (neck, shoulder, flank and thigh). A total of eighty (80) samples from twenty (20) carcasses were analysed. Bacteriological analysis was achieved according to APC. ISO 4833: 2003; ISO 21528-2 and ISO 6579: 2002 norms, respectively for evaluate the aerobic plate count, enteric bacteria count, and qualitative detection of Salmonella. Results: Results varied according to carcass parts, with no significant difference between the bacterial loads of these parts regarding the APC. However, a significant difference was observed between the load in enteric bacteria between the neck and the thigh. With respect to EC regulations (N° 2073/2005), the thigh is the most contaminated part with 100% unsatisfactory results for APC, as well as, enteric bacteria count together with high contamination by Salmonella (detected in 75% of thigh samples). Then following the shoulder, showing 100% unsatisfactory results for APC and enteric bacterial load with presence of Salmonella in 55% of samples. Conclusions: Although being the most contaminated site, the inner part of the thigh had the lowest contamination level with respect to APC.
Keywords: Carcass; Slaughterhouse; Cattle; Surface contamination